An apprenticeship project: Silversmithing in Kapalıçarşı (the Grand Bazaar. Issue 1 (1st March 2019) - Tarcan, Berilsu; Cox, Ayça Tunç
Various cultural objects, crafts and traditional production techniques from Turkey have been research subjects in the field of design studies in recent years. During this time, definitions of tradition, culture and craft have changed and, therefore, these changes need to be revisited, in particular relating to product design. This study explores these changes through a field study conducted in Istanbul, Turkey, one of the key areas of craft production. Focusing on silversmithing, a traditional craft in Turkey, the study seeks to identify new ways in which craft can be used in and lead to the design of new products. The field study was conducted with students from the Industrial Design Department of İstanbul Bilgi University during their second-year studio course. For the study, they were paired with craftsmen in the Kapalıçarşı (the Grand Bazaar) area, one of the most well-known and historic craft neighbourhoods in İstanbul. The aim was to investigate the relationship between traditional craft methods, craft knowledge and contemporary product design, specifically to find out how traditional craft knowledge and methods can be used to inform contemporary product design, and in return, how the craftspeople might benefit from this exchange.